The variation of organic carbon concentrations in the surface water in Cua Luc Bay, Ha Long Bay, Vietnam - Dinh, Hai Ngoc; Duong, Thanh Nghi; Pham, Thi Kha; Le, Van Nam; Cao, Thi Thu Trang; Nguyen, Dac Ve (Vietnam Journal of Marine Science and Technology, 2024)
The total organic carbon (TOC) in the marine environment, which includes dissolved organic carbon (DOC) and particulate organic carbon (POC), is essential to the ocean’s carbon cycling system. This research was carried out in 2023 to assess the variation in organic carbon concentration in the environment of Cua Luc Bay and Ha Long Bay at 22 survey stations. The results show that the average concentrations of DOC and POC are 1.59 ± 0.21 mgC/L and 0.74 ± 0.35 mgC/L, respectively. However, DOC and POC concentrations are still considered low compared with other rivers and estuaries in Vietnam and worldwide. The ratios of organic carbons like DOC/POC and POC/Chl-a in this study area were also calculated. The ratios’ results are evidence of many fluctuations in the water environment in Ha Long Bay, Vietnam, in 2023.